The Many Faces of Sagittal Synostosis: A Novel Classification and Approach to Diagnosis. Issue 1 (January 2022) - Diab, Jason; Flapper, Walter; Grave, Benjamin; Abou-Hamden, Amal; Anderson, Peter; Moore, Mark
Abstract : Purpose: Among the variable forms of craniosynostosis, sagittal synostosis represents the most common type of nonsyndromic single-suture fusion. There are many variations of this form that have been recognized in the literature. We aim to identify and categorize the clinical and radiological characteristics for patients with sagittal synostosis from 2014 to 2017. Secondly, to define a classification system wherein quantitative and qualitative descriptors are used to provide a better understanding of the disease process. Methodology: An institutional retrospective analysis identified all patients during the 2014 to 2017 period with computer tomography (CT) diagnosed single suture sagittal craniosynostosis (n = 51). Redo cases were excluded from the study. The data was collected from CT radiological evidence, clinical images, and medical notes. The patients were stratified into clinical assessment, radiological and neurological, and a statistical analysis was performed. Results: The average age for CT scans was 3 months and operative management 6.4 months, respectively. The most common presentation: Complete synostosis of anterior, central, and posterior (n = 31). Frontal and interhemispheric subarachnoid space (n = 23). Clinical appearance of sagittal ridge, occipital bullet, and frontal (n = 13) and occipital and frontal (n = 13). Conclusions: Sagittal synostosis presented with many heterogeneous variations. The classic appearance of a sagittal ridge, occipital bullet and/or frontal bossing, with frontal interhemispheric and subarachnoid spaces, and complete sagittal fusion was most common. A holistic classification can aid in the assessment and prioritization of surgical intervention. Future longitudinal studies would provide additional insight into the relationships between clinical appearance and suture fusion. Abstract : Supplemental Digital Content is available in the text